Prototype Automatic Cargo Lift - Hanif, Izzuddin; Rahmi, Wildatur; Djatmiko, Wisnu (LPPM Universitas Negeri Jakarta, 2014)
This final project aims to design a device that provides convenience in sending goods vertically and reduce direct contact with the elevator man to become better security. The design was made for the three floors with each floor equipped RFID reader, arduino nano modules and sensors as detecting goods. The method used is an experiment with three (3) parts: the input block, block the process and output block. Input block consists of sensors, process block consists of arduino and output block consists of a DC motor. Prototyping Automatic Cargo lifts performed in the second semester of the academic year 2013/2014 100. The process of making Power Workshop held in Electrical Engineering, Faculty of Engineering, University of Jakarta. Tugas Akhir ini bertujuan untuk merancang perangkat yang memberikan kemudahan dalam mengirim barang secara vertikal dan mengurangi kontak langsung lift dengan manusia agar keamanan menjadi lebih baik. Rancangan dibuat untuk tiga lantai dengan setiap lantainya dilengkapi reader RFID, modul arduino nano dan sensor sebagai pendeteksi barang.Metode yang digunakan adalah eksperimen dengan 3 (tiga) bagian yaitu: blok input, blok proses dan blok output. Blok input terdiri dari sensor, blok proses terdiri dari arduino dan blok output terdiri dari motor DC. Pembuatan Prototipe Automatic Cargo Lift dilakukan pada semester genap 100 tahun akademik 2013/2014. Proses pembuatan dilaksanakan di Bengkel Listrik Teknik Elektro, Fakultas Teknik, Universitas Negeri Jakarta.